Stabilization of emulsified edible coating using cellulose nanomaterials for fruit preservation - Wardana, Ata Aditya; Marcellino, Vincensius; Wigati, Laras Putri; Nkede, Francis Ngwane; Tanaka, Fumina; Tanaka, Fumihiko (Frontiers in Sustainable Food Systems, 2025)
Fruit losses during postharvest handling remain a major global challenge. Edible coatings, particularly those stabilized by cellulose nanomaterials (CNM), offer a sustainable solution to enhance fruit preservation. This review aims to explore the role of CNM-stabilized Pickering emulsions in improving coating stability, antimicrobial activity, and barrier properties. The findings indicate that CNM possess a high aspect ratio, enabling them to create a compact and efficient interfacial layer at the oil-water interface. Incorporating CNM as a stabilizer enhances the barrier properties of emulsion-based coatings, effectively delaying fruit ripening by slowing the respiration rate through mechanisms such as improved inhibition of gas exchange, reduced oxygen availability, and suppression of ethylene production. The effectiveness in reducing microbial growth is attributed to the sustained-release capability of the active components by CNM in the Pickering emulsion coating. Its antimicrobial activity against Gram-positive and Gram-negative bacteria, yeast, and fungi at appropriate concentrations. The optimization of CNM-based Pickering emulsions should be tailored to the specific requirements of the intended application, particularly considering the potential of CNM to serve as a growth medium for microbes. Future work should focus on formulation optimization for industrial application and on sensory evaluations to ensure consumer acceptance, paving the way for CNM as a viable strategy in sustainable fruit preservation.